Acquired TERT promoter mutations activate TERT expression in mantle cell lymphoma - Panero, Julieta (2016)
Mantle cell lymphoma (MCL) is an aggressive lymphoid neoplasm with poor prognosis. Acquired telomerasereverse transcriptase gene promoter (TERTp) mutations are among the most frequent somatic non-codingmutations in cancers. In this study, the prevalence of TERTp mutations in 24 MCL and 21 other lymphoidneoplasias (oLN) was investigated. Eight MCL samples (33%) carried TERTp mutations, two homozygous andsix heterozygous (seven C228T and one C250T), which directly correlated with higher TERT transcription,mitochondrial DNA copy number, and IGHV mutational status in MCL neoplastic cells. TERTp mutations werenot found in oLN. TERTp mutations correlated with more lymphoma proliferation and tumor burden, assuggested by the higher number of lymphoma cells circulating in peripheral blood, and tended to associatewith longer MCL telomeres, especially in homozygous mutants, although not statistically significant.Telomere-biology genes were overexpressed in MCL cells in comparison to healthy lymphocytes, but werenot influenced by mutation status. The findings described for the first time that acquired TERTp mutationsare common in MCL but not in other lymphoid neoplasms. It was also demonstrated that TERTp mutationsassociated with higher TERT mRNA expression in MCL cells in vivo and higher tumor burden, suggestingthese mutations as a driver event in MCL development and progression.